Compensation for moral damage caused to higher education institutions due to the war - S. O. Popova; V. O. Hlazkova (Law and Safety)
The article is devoted to the study of the possibilities for higher education institutions to apply for compensation for moral damage caused by war. The legal framework of higher education institutions is analysed. In particular, it is noted that their main objectives are to ensure that persons obtaining higher education receive the appropriate degree in their chosen specialties through high-level educational activities. It is concluded that due to the armed aggression of the Russian Federation against Ukraine, it is impossible to fulfil this task in full. At the same time, it is noted that military actions violate the personal non-property rights of a legal entity such as a higher education institution. It is determined that the violation of the right to inviolability of business reputation is the basis for compensation for non-pecuniary damage to legal entities. The concept of business reputation is analysed in Ukrainian legislation and legal doctrine. The author's definition of the business reputation of a higher education institution is formulated as an assessment of the quality of scientific, scientific and technical, innovative and/or methodological activities of pedagogical, scientific and pedagogical and scientific employees of an institution licensed to conduct educational activities at the relevant levels of higher education. The article considers the problems faced by higher education institutions due to the war and which lead to a deterioration in their business reputation,